Postural orthostatic tachycardia syndrome following open thoracoabdominal aortic aneurysm repair. Issue 2 (16th February 2021) - Manuel, Lucy; Fong, Laura S; Mamo, Andrew; Varcoe, Ramon; Saw, Wilfred; Grant, Peter
Abstract: Postural orthostatic tachycardia syndrome (POTS) is a variant of cardiovascular autonomic disorder characterised by an excessive heart rate on standing and orthostatic intolerance. We present a rare case of a 38-year-old man who underwent open repair of a thoracoabdominal aortic aneurysm for a chronic Stanford type B aortic dissection whose recovery was complicated by POTS. He received blood transfusions and was commenced on metoprolol, fludrocortisone and ivabradine with significant improvement in his symptoms. Correct assessment of postoperative tachycardia including postural telemetry is the key to identifying this condition and its successful management.